Подскажите пожалуйста решение следующего примера:

(x-t) *(x^2+2xt-3t^2)

1

Ответы и объяснения

2013-11-25T16:39:04+04:00
Я думаю так.
Выражение: (x-t)*(x^2+2*x*t-3*t^2)
Ответ: x^3+x^2*t-5*x*t^2+t^3*3
Решаем по действиям:
1. (x-t)*(x^2+2*x*t-3*t^2)=x^3+x^2*t-5*x*t^2+t^3*3
  (x-t)*(x^2+2*x*t-3*t^2)=x*x^2+x*2*x*t-x*3*t^2-t*x^2-t*2*x*t+t*3*t^2
  1.1. x*x^2=x^3
      x*x^2=x^(1+2)
    1.1.1. 1+2=3
  1.2. x*x=x^2
      x*x=x^(1+1)
    1.2.1. 1+1=2
  1.3. x^2*2*t-t*x^2=1*x^2*t
  1.4. t*t=t^2
      t*t=t^(1+1)
    1.4.1. 1+1=2
  1.5. -x*3*t^2-t^2*2*x=-5*x*t^2
  1.6. t*t^2=t^3
      t*t^2=t^(1+2)
    1.6.1. 1+2=3